Desenvolvimento, caracterização físico-química, estudo da liberação in vitro e avaliação da fotoestabilidade de nanopartículas contendo dapsona e óleo de arroz bruto - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Dapsone is a sulfone with antibiotic activity used for chronic skin diseases such as psoriasis. The use of dapsone by oral route presents high incidence of adverse events. An approach to reduce side effects is the application of dapsone directly into the skin, which can be done by use of nanocapsules (NC), in order to increase the skin permeability of the drug. The rice (Oryza sativa) oil is a component that can be used as NC oil core due to its moisturizing, humectant, antioxidant and UV protection properties. Thus, this study aimed to develop and characterize dapsone-loaded NC using different polymers - poly-ε-caprolactone (NC-P) and Eudragit® RS100 (NC-E) - using different rice oil and drug concentration. The NC showed slightly acidic pH, particle diameter less than 334 nm, narrow particle size distribution, negative zeta potential (-9.9 to -33.7 mV) and encapsulation efficiency higher than 83%. The in vitro release study, carried out in dialysis bags, showed that both NC were effective in controlling the release of dapsone. The monoexponential equation was the most appropriate model to describe the release profiles. The nanoencapsulation decreases photolytic degradation of dapsone in UVA light, yielding drug remaining percentage of 80.6%, 91.9% and 1.4% for NC-P1, NC-E and free drug, respectively. In addition, hydrogels prepared with NC-P1 (HG-NCP1) and NC-E (HG-NCE) showed pH suitable for cutaneous application, content close to 100% and non-Newtonian pseudoplastic (HG-NCE) or plastic (HG-NCP1) behavior. In vitro occlusion evaluation showed that the HG-NCP1 significantly increased the occlusion factor when compared to HG-NCE and the free drug hydrogel. Thus, these formulations are promising systems for topical application of dapsone, with the potential to constitute in an effective topical treatment for psoriasis.
Development, physicochemical characterization , in vitro release of the study and evaluation of nanoparticles containing dapsone photostability and crude rice bran oil
Keywords: Psoríase; Dapsona; Óleo de arroz; Nanocápsulas; Liberação in vitro; Fotoestabilidade; Psoriasis; Dapsone; Rice oil; Nanocapsules; In vitro release; Photostability; CNPQ::CIENCIAS BIOLOGICAS